The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hon.2943
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for a rapidly evolving landscape in chronic lymphocytic leukemia management

Abstract: With the advent of targeted therapies for chronic lymphocytic leukemia (CLL), treatment choice has expanded and patients are living longer. Careful consideration is needed regarding treatment duration and sequence, how best to meet patients' needs, balancing toxicities while improving long-term survival and maximizing depth of response. This review addresses these considerations and discusses current targeted treatment dilemmas. Targeted therapies have dramatically transformed the CLL treatment landscape. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…With a fixed-duration approach, Bcl-2i venetoclax can achieve deep remissions, resulting in high rates of uMRD in treatment-naive and r/r CLL patients [ 31 , 43 , 44 ]. In contrast, BTKi such as ibrutinib and acalabrutinib seldom achieve a complete remission or uMRD status but still produce high ORR, long-term disease control, and survival benefits [ 50 ]. Ongoing studies are now evaluating the clinically complimentary activity of BTKi and Bcl-2i as combination therapies [ 31 , 50 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…With a fixed-duration approach, Bcl-2i venetoclax can achieve deep remissions, resulting in high rates of uMRD in treatment-naive and r/r CLL patients [ 31 , 43 , 44 ]. In contrast, BTKi such as ibrutinib and acalabrutinib seldom achieve a complete remission or uMRD status but still produce high ORR, long-term disease control, and survival benefits [ 50 ]. Ongoing studies are now evaluating the clinically complimentary activity of BTKi and Bcl-2i as combination therapies [ 31 , 50 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In contrast, BTKi such as ibrutinib and acalabrutinib seldom achieve a complete remission or uMRD status but still produce high ORR, long-term disease control, and survival benefits [ 50 ]. Ongoing studies are now evaluating the clinically complimentary activity of BTKi and Bcl-2i as combination therapies [ 31 , 50 ]. The treatment combination of BTKi (ibrutinib) and Bcl-2i (venetoclax) in first-line [ 51 ] and r/r [ 52 ] treatment settings in clinical trials showed a high uMRD rate of 36% in r/r CLL patients [ 52 ] and 61% in untreated high-risk and older patients with CLL [ 51 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Clinical management of chronic lymphocytic leukemia (CLL) patients has been transformed by the introduction of targeted therapies that disrupt tumor microenvironmental signals, leading to enhanced survival rates of poor-prognostic patients, highlighting a potential curative strategy [ 1 ]. However, these treatments are not suitable for all CLL patients and the development of drug resistance has been demonstrated [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical management of chronic lymphocytic leukemia (CLL) patients has been transformed by the introduction of targeted therapies that disrupt tumor microenvironmental signals, leading to enhanced survival rates of poor-prognostic patients, highlighting a potential curative strategy ( 1 ). However, these treatments are not suitable for all CLL patients, and the development of drug resistance has been demonstrated ( 2, 3 ).…”
Section: Introductionmentioning
confidence: 99%